The other walls : the Arab-Israeli peace process in a global perspective - Saunders, Harold H. (Princeton legacy library., 1991)
Drawing on intensive firsthand experience gained during the most successful years of Arab-Israeli peace negotiations, Harold Saunders explains the complexities of the peace process: it was not just a series of negotiated agreements but negotiation embedded in a larger political process. In the first edition of The Other Walls, Saunders argued persuasively that until leaders change the political environment by lowering the human and political barriers to peace, negotiators stand little chance. Now he places that focus on political process in the context of a new world-where familiar concepts o.